Social Awareness of Entrepreneurs Towards Product Halal Certificates - Dandi Darmadi; Vidya Imanuari Pertiwi; Oktarizka Reviandani (JURNAL ILMU SOSIAL, 2022)
Food and beverage production are increasingly circulating, whether produced by large companies or small businesses. The public, as consumers, needs a guarantee of the hygiene and halalness of a product, so the Government requires a halal certificate that business actors must pocket before their products are sold. Of 479,621 new business units in East Java, 2,230 have halal certificates. The author's concern is analyzing business actors' social awareness toward halal certificates. The research was conducted with a qualitative approach, sourced from primary and secondary data. Data collection techniques are interviews, observation, and literature study. The study's results using the Social Awareness theory, which looked at the knowledge, attitude, and action aspects, found that business actors' knowledge of halal certificates and procedures was well established. However, in terms of attitudes and actions towards halal certificates, the products differed due to external factors, namely costs and management complexity. Business actors will be proactive if obtaining halal product certificates is carried out efficiently and at low costs. Even producers admit they want to avoid taking care of if they have to use personal costs. Another factor that supports the social awareness of business actors is the assistance of facilities from the Surabaya city government through the Department of Trade, both technical assistance and costs.